Asymmetry patterns are associated with body size and somatic robustness among adult !Kung San and Kavango people - Kirchengast, Sylvia (Anthropological Review, 2019)
Asymmetry of bilateral anatomical structures is widely found in nature. Fluctuating asymmetry, i.e. mostly tiny random deviations from perfect symmetry in bilateral structures, is mainly interpreted within the framework of developmental instability. This interpretation is mainly due to the fact, that higher fluctuating asymmetry is often found in association with various pathological conditions but also from increased stress during somatic development. Directional asymmetry, in contrast, describes a distinct pattern of bilateral variation in a group of individuals, characterized by the tendency to find the larger side mainly at the same side for all individuals. This kind of asymmetry is mostly caused by behavioral lateralization. Somatic stress during development affect not only asymmetry patterns, it is has also an adverse effect on somatic growth. Therefore, the present study tested the hypothesis, that increased asymmetry is associated with decreased body height as well as postcranial length and robustness dimensions. The association patterns between fluctuating as well as directional asymmetry and parameters of somatic growth and robustness are analyzed among 236 !Kung San and 248 Kavango people of Namibia between the ages of 18 and 65 years. Fluctuating asymmetry was determined by ear length and ear breadth. Directional asymmetry was determined by hand length and hand breadth dimensions. Fluctuating as well as directional asymmetry correlated significantly negatively with body height and length dimensions, the correlations however, were weak. The results are interpreted as a corroboration of the theory that developmental stress may increase fluctuating asymmetry but on the other hand may decrease body size.